Enter B and W: two new meningococcal vaccine programmes launched. - Ladhani, S; Ramsay, M; Borrow, R; Riordan, A; Watson, J; Pollard, A (BMJ Publishing Group, 2016)
In 2015, the UK became the first country in the world to have a comprehensive routine meningococcal vaccine programme targeting all of the main capsular groups of N. meningitidis. 1 An infant vaccine programme against meningococcal capsular group B Neisseria meningitidis (MenB) was launched from 1st September with an aim to reduce endemic MenB disease in early childhood. On 1st August 2015, an adolescent programme against groups A, C, W and Y meningococci (MenACWY) was rolled out to halt a growing outbreak of capsular group W disease (MenW) caused by a hypervirulent clone of N. meningitidis, in addition to maintaining control against MenC disease provided by the current adolescent programme. 2.